Hip joint degeneration - not only an issue of the elderly - Wojciech Rutkowski; Natalia Gajdzińska; Adam Salwa; Weronika Rostkowska; Maciej Rzepka; Karolina Sztuba; Justyna Puchała; Katarzyna Rymaszewska; Dominika Starzomska; Karolina Basiura (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Legg-Calve-Perthes Disease (LCPD) is a condition characterized by ischemia of the proximal femoral epiphysis, leading to pain, limping, and potential hip joint deformities in children. Its etiology remains unclear, with theories implicating repetitive microtrauma, skeletal retardation, and vascular insufficiency. Diagnosis involves radiological assessment and classification systems to monitor disease progression, influencing treatment decisions and long-term outcomes. Material and methods: This study summarizes existing literature and clinical data on LCPD, focusing on etiological theories, diagnostic methods, treatment strategies, risk factors, and prognostic indicators. Information was gathered from medical databases, peer-reviewed journals, and case studies to compile a comprehensive overview of the disease. Aim of study: The aim was to gather current knowledge on LCPD, emphasizing diagnostic approaches, treatment modalities, and factors influencing clinical outcomes. Special attention was given to discussing the efficacy of various treatment options and identifying prognostic factors that impact the disease trajectory. Conclusion: Effective management of LCPD hinges on early diagnosis, appropriate treatment selection, and careful monitoring of disease progression. Prognosis is influenced by factors such as age at diagnosis, extent of femoral head involvement, and maintenance of hip joint congruence. Further research is needed to refine treatment protocols and improve long-term outcomes for affected children.